(untitled) (Fiep Bulletin - online, 2014)
This study is justified by identifying the roles and implications of the work of the Educational Director in the school context in view of the importance of quality education . Therefore, it is necessary to understand the role and function of the director once in private schools , is not always the full faculty . The work of the Director , then, is a journey triple administrator , coordinator and manager , a fact that overloads the same compromising the quality of their work , the work of the faculty and the quality of teaching and learning. Also discussed will be the role of pedagogical coordinator with regard to the articulation of teaching . For the realization of the objectives proposed a survey was conducted on books , journals , articles and websites that discuss about it and also a documentary research in the School Creativity . From the results collected showed that the democratic management has the basic principle that it is not only an administrator making the decisions , but they must be taken collectively. Education management should be seen as a practical joint directors , coordinators , teachers , administrative officers , government and society.